Onion, Tree—Allium cepa L. (Proliferum group) - James M. Stephens (EDIS, 2003)
This document describes the tree onion (Allium cepa L., Proliferum group), also known as Egyptian onion or walking onion. It outlines the plant’s unique growth habit—producing bulbils at the top instead of flowers—and provides guidance on cultivation, including planting methods and spacing. The tree onion is typically grown as an annual in Florida, with fall planting yielding the best results. Both the base and top bulblets are edible, commonly used fresh or pickled. Original publication date May 1994.